2007
DOI: 10.1177/0340035207080300
|View full text |Cite
|
Sign up to set email alerts
|

Library and Information Services in South Africa: an overview

Abstract: Opening with a review of information policy, the article describes information sources, systems and services in South Africa, embedding them in the wider national information system. A description of the library and information education and training sector and the organized profession follow. This overview is based on literature retrieved from the available, mostly electronic, databases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The authors found in that study that only few librarians from South Africa mentioned lack of skills and facilities. Research statistics show that African countries lag behind those in the rest of the world in the development of ICT infrastructure (Ojedokun and Lumande, 2005; Stilwell, 2007). This adversely affect the acquisition of digital literacy skills by librarians in the African region.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…The authors found in that study that only few librarians from South Africa mentioned lack of skills and facilities. Research statistics show that African countries lag behind those in the rest of the world in the development of ICT infrastructure (Ojedokun and Lumande, 2005; Stilwell, 2007). This adversely affect the acquisition of digital literacy skills by librarians in the African region.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Research statistics show that African countries lag behind those in the rest of the world in the development of ICT infrastructure (Ojedokun and Lumande, 2005; Stilwell, 2007). However, this is not exactly the case in South Africa and in South African universities in particular, which enjoy a high level of ICT integration and adequate ICT infrastructure.…”
Section: Contextualisation and Problematisationmentioning
confidence: 99%
“…Education for library and information work in South Africa commenced in 1933 and its development is described elsewhere (Stilwell, 2007a). Today, eleven institutions offer LIS education and training.…”
Section: Education and Trainingmentioning
confidence: 99%
“…
An update of an article which appeared in the IFLAjournal (Stilwell, 2007a Keywords: Library and information systems and services; access to information; education and training; South Africa I Introduction In this article we pick up on the critical questions of the school library sector before reviewing other information services. As with Part I of this two part article, Boon's four broad categories (1992) for the information sector are used for structuring much of the contents.
…”
mentioning
confidence: 99%